Metode Penelitian Ilmiah Karakteristik dan Potensi Bakteri Asam Laktat (BAL) pada Makanan Khas Melayu (Tempoyak) sebagai Agensi Probiotik - Nawra Nurvidilla; Ardi Mustakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Cell-based therapy is an innovative approach currently experiencing rapid development in the biomedical field, particularly in the areas of immunotherapy and gene therapy. This approach utilizes living cells, such as genetically modified T cells, to recognize and destroy abnormal cells such as cancer cells or cells with genetic mutations. The development of gene engineering technologies, such as CRISPR/Cas9, has enabled scientists to precisely edit damaged genes, thereby repairing or restoring normal cell function. This study aims to examine recent advances in cell-based therapy, focusing on cell modification techniques, the efficiency of the immune system in targeting cancer cells, and the integration of gene therapy technology and immune cells. Furthermore, this study also identifies several challenges that remain, including the risk of side effects due to undesirable immune reactions, the genetic stability of the modified cells, and the long-term sustainability or viability of transplanted cells. While these challenges remain serious concerns, several clinical studies have shown that cell-based therapy has significant potential in the treatment of difficult-to-treat diseases, such as advanced cancer and rare genetic disorders. The results of this study demonstrate that cell-based therapy not only offers a new approach to treatment but also opens the door to more personalized and precise therapies. However, for broader implementation in clinical practice, further, in-depth research is needed regarding safety, long-term efficacy, and strict regulation. This research is expected to make a significant contribution to the development of more effective and safe future therapies.